2021
DOI: 10.1186/s12876-021-01659-y
|View full text |Cite
|
Sign up to set email alerts
|

Impact of improvement of sleep disturbance on symptoms and quality of life in patients with functional dyspepsia

Abstract: Background/aims Functional dyspepsia (FD) is often comorbid with sleep disturbance. However, it is not fully understood how sleep disturbance affects the pathophysiology of FD. We aimed to investigate the relationship between FD and sleep disturbance. Methods We prospectively enrolled 20 FD patients with sleep disturbance between December 2018 and July 2019. Patients took sleep aids for 4 weeks and filled out questionnaires before and after taking … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 67 publications
0
5
0
Order By: Relevance
“…In patients with IBS, more waking episodes during sleep was predictive of more abdominal pain ( 38 ), GI distress, and worse quality of life but not bowel consistency or frequency ( 37 ). One study demonstrated that improving sleep quality using prescription sleep aids improved GI symptoms and quality of life in patients with functional dyspepsia ( 40 ). Poor sleep quality has been associated with increased nausea, fatigue, and abdominal pain in children and adolescents with disorders of gut brain interaction ( 41 ).…”
Section: Discussionmentioning
confidence: 99%
“…In patients with IBS, more waking episodes during sleep was predictive of more abdominal pain ( 38 ), GI distress, and worse quality of life but not bowel consistency or frequency ( 37 ). One study demonstrated that improving sleep quality using prescription sleep aids improved GI symptoms and quality of life in patients with functional dyspepsia ( 40 ). Poor sleep quality has been associated with increased nausea, fatigue, and abdominal pain in children and adolescents with disorders of gut brain interaction ( 41 ).…”
Section: Discussionmentioning
confidence: 99%
“…Improvement of insomnia by the administration of sleep aids (eszopiclone, zolpidem, and suvorexant) resulted in improvement of gastrointestinal symptoms and quality of life in patients with FD. This effect may be related to pain modification [39].…”
Section: Discussionmentioning
confidence: 99%
“…A relationship between functional dyspepsia and insomnia has also been suggested [37, 38]. Hypnotics were previously shown to attenuate dyspeptic symptoms [39]. However, the mechanisms responsible for the amelioration of functional dyspepsia have yet to be elucidated.…”
Section: Discussionmentioning
confidence: 99%